Východolašská nářečí versus gwara zachodniocieszyńska, czyli dialektologiczna wojna o Zaolzie - Irena Bogocz (Ksiegarnia Akademicka Publishing, 2017)
Eastern Lachian Dialects vs. Western Lachian Dialects or the Dialectological Battle for the Zaolzie Region The article is devoted to the historical discussion which arose around the affiliation of the inhabitants of the Czech–Polish border area with the Czech or the Polish nationality and language. The bone of contention was the dialect used in the Czech part of the Cieszyn/Těšín region. Although the discussion was generally conducted in academic circles, it was also picked up on by the local press (i.e., the cultural monthly “Zwrot”). It concerned not only the interests of Czech (Czechoslovak) and Polish dialectology, but also posed existential questions for the Polish minority living in this part of former Czechoslovakia. The article describes the basic theses published in the 1950s–1970s. Engaged in the discussion were, among others, Adolf Kellner (who originated the debate with the publication of Východolašská nářečí I., II., ‘Eastern Lachian Dialects I., II.’ in 1946 and 1949 respectively), Jaromír Bělič, Arnošt Lamprecht, and, representing predominantly the attitudes of Polish dialectology, Karol Dejna. The polemics were marked by the Marxist ideology of the time, and the overall policy of the Czechoslovak state, which intent was to justify the affiliation of certain linguistic areas to Czechoslovakia.